Amine modification of calcium phosphate by low-pressure plasma for bone regeneration - Kodama, Joe; Harumningtyas, Anjar Anggraini; Ito, Tomoko; Michlíček, Miroslav; Sugimoto, Satoshi; Kita, Hidekazu; Chijimatsu, Ryota; Ukon, Yuichiro; Kushioka, Junichi; Okada, Rintaro; Kamatani, Takashi; Hashimoto, Kunihiko; et al. (Scientific reports, 2021)
Regeneration of large bone defects caused by trauma or tumor resection remains one of the biggest challenges in orthopedic surgery. Because of the limited availability of autograft material, the use of artificial bone is prevalent; however, the primary role of currently available artificial bone is restricted to acting as a bone graft extender owing to the lack of osteogenic ability. To explore whether surface modification might enhance artificial bone functionality, in this study we applied low-pressure plasma technology as next-generation surface treatment and processing strategy to chemically (amine) modify the surface of beta-tricalcium phosphate (β-TCP) artificial bone using a CH4/N2/He gas mixture. Plasma-treated β-TCP exhibited significantly enhanced hydrophilicity, facilitating the deep infiltration of cells into interconnected porous β-TCP. Additionally, cell adhesion and osteogenic differentiation on the plasma-treated artificial bone surfaces were also enhanced. Furthermore, in a rat calvarial defect model, the plasma treatment afforded high bone regeneration capacity. Together, these results suggest that amine modification of artificial bone by plasma technology can provide a high osteogenic ability and represents a promising strategy for resolving current clinical limitations regarding the use of artificial bone.
Keywords: regenerace kostí; krysa rodu Rattus; kostní náhrady; fosforečnany vápenaté; buněčná diferenciace; Calcium Phosphates; Osteogenesis; transplantace kostí; Animals; Bone Regeneration; biokompatibilní materiály; Rats; Biocompatible Materials; osteogeneze; zvířata; Bone Transplantation; Cell Differentiation; Bone Substitutes